2008
DOI: 10.1111/j.1754-4505.2008.00038.x
|View full text |Cite
|
Sign up to set email alerts
|

Virtual patient instruction for dental students: can it improve dental care access for persons with special needs?

Abstract: An interactive, virtual-patient module was produced on compact disc (CD-ROM) in response to the critical need to increase dental students' clinical exposure to patients with developmental disabilities. A content development team consisting of dental faculty members, parents of children with developmental disabilities, an individual with a developmental disability, and educational specialists developed the interactive, virtual-patient module. The module focused on a young man with congenital deafblindness prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 16 publications
1
40
0
3
Order By: Relevance
“…Rather than simply relying on didactic instruction, experiential learning with reflective components is recommended for training dental students about care of people with intellectual disabilities (Delucia & Davis 2009). Innovative approaches using computer-based training were reportedly effective (Ruiz et al 2006, Kleinert et al 2007) and can be easier to deliver; for example an interactive module featuring a deaf-blind virtual patient (Sanders et al 2008).…”
Section: Different Approachesmentioning
confidence: 99%
“…Rather than simply relying on didactic instruction, experiential learning with reflective components is recommended for training dental students about care of people with intellectual disabilities (Delucia & Davis 2009). Innovative approaches using computer-based training were reportedly effective (Ruiz et al 2006, Kleinert et al 2007) and can be easier to deliver; for example an interactive module featuring a deaf-blind virtual patient (Sanders et al 2008).…”
Section: Different Approachesmentioning
confidence: 99%
“…Studies evaluating the effectiveness of education programmes in special needs dentistry, using a pre‐post design, are rather scarce. Sanders et al found that after completion of an interactive, virtual‐patient module on compact disc, presenting an individual with a developmental disability, students' perceived comfort and knowledge base, has significantly improved. Salama et al reported that viewing an educational presentation in the form of a DVD was effective in informing dental students and providing them with instructive basic information on patients with special healthcare needs.…”
Section: Introductionmentioning
confidence: 99%
“…Janda et al [34] found that the use of VPs improved the capability of dental students to take a health history. Another study [35] investigated the use of VPs in dental care for persons with special needs and concluded that dental students demonstrated improved communication skills and became more effective when caring for such patients.…”
Section: Introductionmentioning
confidence: 99%